Program “Gebrak Stunting” sebagai Upaya Pencegahan Stunting di Desa Sukasenang Kecamatan Sindangkasih - Yuni Nur'afiah; A. Nopian Hendriana (Pancanaka, 2022)
The stunting prevalence rate in Indonesia still tends to be high, about 27.7 percent in 2019. This paper uses a qualitative descriptive method regarding the movement program with cadres in stunting prevention efforts (Gebrak Stunting) analyzed through observations and the author's experience as the manager of the Gebrak Stunting program. A total of 54 cadres were involved in the program and divided into 7 groups based on the hamlets/posyandu assisted. The series of programs consist of cadre training; field practice in the form of counseling, advocacy of figures, assistance to stunting risk targets, and stunting prevention innovations; as well as presentation of the results of the movement in the field and appreciation of the best groups. Data were collected using self-report and observation techniques, then analyzed using descriptive analysis. Some of the achievements of stunting prevention efforts through this program include 1) the average knowledge of cadres increased by 19.8 percent after attending training; 2) trained cadres have successfully practiced stunting prevention efforts in the field for 20 and cadres have also succeeded in providing assistance to targets at risk of stunting. The total beneficiaries of the program are 47 pregnant women, 166 under-aged mothers, and 2,026 other targets.